REGENERATION MEDIA STANDARDIZATION AND MOLECULAR DIVERSITY ANALYSIS IN COTTON CULTIVARS - A. A. BHAROSE; S. A.THAKUR; D. N. DAMSE (The Bioscan, 2014)
A direct and indirect shoot regeneration protocol of three cotton cultivars viz. BN-1, PA-255, and PA-08, was optimized. Comparative studies on in vitro regeneration from shoot tip, cotyledonary node, hypocotyls and leaf explants revealed considerable variability in response to plant growth regulators. MS Basal formulation with combination of the cytokinins benzylaminopurine (2mg/l) and kinetin (1mg/l) shown 30-50% maturity response for cotyledonary node and shoot tip explants supplemented with kinetin (0.1mg/l) shown 28-42% matured plants, while callus initiation (35-71%) was observed in medium supplemented with 2, 4-D (0.1mg/l) as auxin source and kinetin (0.5mg/l) as cytokinin source when leaves as explants and hypocotyls shown callusing (3564%) when KNO3 (1.9g/l) was used in addition. By second objective 7 genotypes viz. BN-1, PA-255, PA-08, AC738, PA-402, PA-183 and PA-405 were characterized by ten RAPD primers. Total 67 bands were produced out of which 63 bands were polymorphic while 4 bands were monomorphic. The average genetic similarity coefficient value was 0.392. Dendrogram was developed for RAPD analysis using NTSYS-pc Software. It showed 2 super clusters. Significant similarities were found in the clustering of RAPD Analysis.